Still walking in the light - Rydstrom, Darren; Mardoyan, Mark.; African Children's Choir; Music for Life Institute (Bellingham, WA : Music for Life Institute, African Children's Choir, 2000)
Video of the African Children's Choir's 15th anniversary concert on January 14, 2000, with special guests, the Young Africans.
DVD; NTSC.
African Children's Choir.
Photographed by Martin Mate; music by Keith Getty.
Not rated.
Keywords: African Children's Choir; Young Africans (Musical group); Gospel music; Contemporary Christian music; Choruses, Sacred (Children's voices); Concert films